te Social Responsibility (CSR) and Good Corporate Governance (GCG) Influence on Corporate Financial Performance - Yendrawati, Reni; Kinanti, Amalia (Jurnal Akuntansi dan Auditing Indonesia, 2024)
The aim of this research is to analyze the influence of CSR which will be viewed from CSR disclosures carried out by the company and GCG PROXIED by institutional ownership, managerial ownership and an independent board of commissioners on the company's financial performance. The population in this research is manufacturing companies listed on the BEI in 2019 - 2021. Sampling used the purposive sampling method that collected 37 companies. The analysis was multiple linear regression analysis. The results of this research indicate that corporate social responsibility, institutional ownership and managerial ownership do not affect on financial performance. Independent board of commissioners has a positive effect on financial performance. The results of this research are expected to provide the government an evaluation material regarding corporate social responsibility regulations.